Efforts to Increase the Effectiveness of Learning the Qur'an By Using the Group Tutor Method - Baeti Inna Nur Janah; Sugiyono Sugiyono (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The purpose of this study is to find out the method of group tutors can improve children's ability to read the Qur'an according to tajwid in Sidoharjo village to find out the extent to which the group tutor method can improve the ability of children to read the Qur'an according to tajwid in Sidoharjo village. This type of research uses quantitative methods. Meanwhile, data analysis uses cumulative frequency analysis. The subjects in the study were children in Sidoharjo village based the results of the study showed that the group tutor method in the learning process that by using the group tutor method to increased the effectiveness of learning the Qu'ran. The increase in effectiveness occurs due to the management of the learning process in groups with heterogeneous backgrounds of children with abilities Learning using the group tutor method can increase the effectiveness of children, the average effectiveness time reaches 71.9%.